Engineered red blood cell extracellular vesicles for delivery of Dox and siIDO1 enhance targeted chemo-immunotherapy of acute myeloid leukemia - Jing Yang; Ling Zhang; Nan Wu; Jiayuan Hu; Jun Ren; Xinyi Chen; Xingyu Wei; Minghui Sun; Ziwei Li; Yongcan Liu; Yan Shu; Genyou Li; et al. (Journal for ImmunoTherapy of Cancer)
Background As a malignancy of hematopoietic origin, the standard-of-care cytoreductive chemotherapy can not provide satisfactory treatment effect for patients with acute myeloid leukemia (AML). Immunotherapy has received increasing attention in leukemia treatment. However, the immunosuppressive microenvironment and low cancer immunogenicity of AML blasts create major obstacles to effectively inducing immune responses.Methods We developed an extracellular vesicle-based dual-delivery biosystem, which enhanced anti-AML immune responses by activating the immunogenicity of leukemia cells and relieving immunosuppression in AML allografted mice. Red blood cell-derived extracellular vesicles (REVs) were selected as delivery carriers due to the excellent biocompatibility. REVs were ligated with leukemia-targeting peptide P9 and subsequently loaded with immunogenic cell death (ICD) inducer (Doxorubicin, Dox) and indoleamine 2,3-dioxygenase-1 siRNA (siIDO1) to construct a chemoimmunological cascade biosystem (REVs-Dox/siIDO1-P9).Results The biosystem can specifically deliver the loaded Dox and siIDO1 into target leukemia cells and was validated capable of inducing efficient ICD. ICD-mediated release of damage-associated molecular patterns synergistically functions with siIDO1-mediated IDO1 silence to effectually recruit CD8+ T cells and enhance CD8+ T cell’s functions. In the AML mouse model, REVs-Dox/siIDO1-P9 can evoke a strong antileukemia response and prolong leukemia-bearing mice survival compared with REVs-Dox/siNC-P9 and REVs-siIDO1-P9.Conclusion Our findings indicate that the extracellular vesicle-based chemoimmunological cascade biosystem provides a novel strategy for AML treatment.